PENGGUNAAN VARIASI UKURAN DIAMETER BUTIR MAKSIMUM AGREGAT KASAR TERHADAP KUAT TEKAN BETON - Aiyub Aiyub (Politeknik Negeri Lhokseumawe, 2011)
This study aims to determine the use of variations in the size of the maximum grain diameter of coarse aggregate on compressive strength of concrete with fas 0.45 by cylindrical test specimen size 15 x 30 cm. Planning mix desing using a modified method of ACI with fas value of 0.45 and the value of the planned 75-100 mm slump. This study includes compressive strength performed at age 7 days and 28 days, treatment is normally carried out with care marinade soaked in the tub for 7 days and 28 days. Compressive strength test results obtained in the test specimen 7 days old premises gravel size is 20.50 Mpa 12.5 mm, 19 mm, 16.99 MPa, 16.76 MPa is 25 mm and 31.5 mm was 14.57 Mpa , while the age at 28 days was 30.51 MPa 12.5 mm, 19 mm, 24.86 MPa, 21.85 MPa is 25 mm and 31.5 mm was 21.66 Mpa. So the smaller the aggregate maximum compressive strength used was obtained by the higher and conversely the greater the maximum aggregate used dihasikan compressive strength lower. keywords: compressive strength, maximum grain diameter